Movement based Learning Cycle for Accelerated functional recovery from physical, mental, cognitive and emotional disorders - BANERJI, Subhasis (2024)
Disclosed is a learning model employed to treat patients with functional impairments due to psychological, mental cognitive or physical disorders or disabilities. The treatment includes accessing at which transition stage of the learning model that a subject has movement transition deficits based on the subject's bio-signals, such as brain state and muscle state signals. The movement transition deficits are addressed so that the subject can attain an upward spiral, accelerating functional recovery or development and avoid a downward spiral towards compensation and slowing down of recovery.